Algae−bacteria interactions that balance the planktonic microbiome. Issue 1 (26th March 2019) - Cirri, Emilio; Pohnert, Georg
Summary: Phytoplankton communities within the photic zones of the oceans and lakes are characterised by highly complex assemblages of unicellular microalgae and associated bacteria. The interconnected evolutionary history of algae and bacteria allowed the formation of a wide spectrum of associations defined by orchestrated nutrient exchange, mutual support with growth factors, quorum sensing mediation, and episodic killing of the partners to obtain more resources. In this review, we discuss how these cross‐kingdom interactions shape plankton communities that undergo annual, seasonal switching between alternative states with balanced multispecies consortia. We illustrate how these microscopic interactions can have consequences that scale up to influence global element cycling.